2000
DOI: 10.1046/j.1523-1755.2000.07422.x
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for selection of ESRD treatment modalities

Abstract: Criteria for selection of ESRD treatment modalities. The most strategy may be based, also, on clinical status, patient important renal replacement therapies (RRT) for end-stage age, patient preference, psychological stability, etiology renal disease (ESRD) patients are hemodialysis (HD), peritoof ESRD, comorbidity, suitable living-related donor, neal dialysis (PD) and renal transplantation (RT). Survival, economic factors and social circumstances. morbidity and quality of life are the main factors to select th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
13
0
5
Order By: Relevance
“…In the United States, in 1996, patients with 65 years or more were 46% of new patients on renal replacement therapy. 10 Despite not being the main primary cause of CKD, diabetes accounts for a greater proportional contribution for patients that began PD than those that in hemodialysis, suggesting a differential allocation of patients between these modalities. In developed countries, the patients on PD are more autonomous, have higher schooling, perform better preparation before initiating RRT and have less comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, in 1996, patients with 65 years or more were 46% of new patients on renal replacement therapy. 10 Despite not being the main primary cause of CKD, diabetes accounts for a greater proportional contribution for patients that began PD than those that in hemodialysis, suggesting a differential allocation of patients between these modalities. In developed countries, the patients on PD are more autonomous, have higher schooling, perform better preparation before initiating RRT and have less comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Death was considered as a fi nal event, and the patients were only censored through loss of follow up or at the end of the study period. 10 In order to indentify an effect independent of the explanatory variables for survival, a multivariate Cox proportional hazard model was used. The proportionality assumption was evaluated by the graphic logminus-log method.…”
Section: Methodsmentioning
confidence: 99%
“…First, patient characteristics are oped countries. Although some clinical conditions should be considered when allocating patients to either HD or PD (19), studies worldwide have shown that there are other factors that are quite important. These include patients' preferences, education, and training of physicians and nurses, as well as nonclinical factors such as financing, reimbursement, resource availability, and sociocultural habits.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic, youngest, and oldest patients had a greater probability of being allocated to PD. In the United States, PD allocation is more closely associated with younger individuals, whereas in France it is a common treatment option for the elderly (2,19,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Vários fatores influenciam a escolha da modalidade de diálise, incluindo as características individuais e clínicas do paciente no início do tratamento, as preferências dos pacientes e mé-dicos e a localização geográfica 3,4,5 . Alguns estudos também têm enfocado a importância de fatores econômicos na escolha da modalidade tais como a forma de pagamento do tratamento e a disponibilidade de recursos 6 .…”
Section: Introductionunclassified